Case report: Full thickness burns from intense pulsed light hair removal - Hugh W. Finlayson; Woo A. Kim; Baljit Dheansa (Elsevier, 2023)
Background: Laser or light therapy hair removal is commonly used for hair removal in beauty salons and other non-medical practices. The process utilises light energy which is absorbed by the melanin in the hair. The subsequent heat energy damages the hair follicles inhibiting or delaying future hair growth. Burn injuries are a very rare side effect of this procedure and more commonly seen in patients with darker skin pigments. Case presentation: We present a case of a 30 year old female who was a delayed presentation of full thickness burns to her right lower leg around a tattoo following hair removal with an intense pulsed light (IPL) device. Conclusions: Burn wounds as a result of light therapy hair removal procedures are very rare. However the involvement of surrounding tattoos in creating excessive heat transfer to surrounding tissue needs to be highlighted. This potential side effect is not often recognised or explained to customers and therefore important to note for providers as light therapy use becomes increasingly popular.